Cybercrime, Citizens' Data Protection, and Electoral Integrity (Oratio Directa, 2023)
Personal-data theft before an election is a criminal act that can damage public trust in electoral processes and results. This qualitative case study, based on literature review, examines cybercrime, weak protection of citizens' data, and their implications for the integrity of Indonesia's 2024 simultaneous elections. The study finds that expanding digital technology is accompanied by increased data theft, frequently driven by economic motives. Weak personal-data protection remains a serious state responsibility, while data leaks provide space for hackers to delegitimize state control over digital-election technology.
Keywords: Cybercrime; Data protection; Digital democracy; Electoral integrity; Personal data